Health-related quality of life in a cohort of youths with type 1 diabetes - Martins,Karina Andressa Khater Fontes (2018)
SUMMARY Health-related quality of life (HRQOL) in type 1 diabetes mellitus (T1DM) has been widely studied. The objectives of this study were to evaluate and identify the factors influencing the HRQOL of children and adolescents with T1DM. MATERIAL AND METHODS: In total, 59 patients (9–16 years, T1DM for ≥1 year) responded to a version of the Diabetes Quality of Life Instrument for Youth (DQOLY) adapted to adapted to Brazilian patients, the Instrumento de Qualidade de Vida para Jovens com Diabetes (IQVJD). This instrument comprises 50 items (domains satisfaction, impact, and concerns, with the lowest scores corresponding to better HRQOL) and a questionnaire gathering social, demographic, and clinical parameters. RESULTS: The mean age of the patients was 13.6 years, and 57.6% were girls. The median age at diagnosis was 7.16 years, 63% presented diabetic ketoacidosis (DKA) at diagnosis and 29% during follow-up. Mean glycated hemoglobin (HbA1c) in the previous year was 10%. All patients administered multiple insulin doses (mean 4.2 applications/day), 74.5% used rapid-acting and intermediate-acting insulin analogs, and 67.8% used pens for insulin application. The results of the DQOLY were within the cutoff limit for better HRQOL. An isolated analysis of each domain and the questionnaire results showed that the following factors were associated with better HRQOL: height Z-score, lower HbA1c, practice of physical activity, use of pen, fewer hospitalizations, and residence in a rural area. There was a high DKA rate at diagnosis, and the metabolic control was inappropriate in most patients. Despite coming from low-income households, most patients had access to the recommended treatment. CONCLUSION: Among T1DM patients, 71% had IQVJD scores compatible with better HRQOL.